ETIKA BISNIS ISLAM - Mutia Dila Puspita; Nina Puspita; Siti Nur Aisah Sitompul (Cahaya Ilmu Bangsa, 2025)
This article examines the significance of Islamic business ethics as a foundation for conduct in business activities. In a corporate setting, ethics refers to the principles that distinguish between acceptable and unacceptable conduct, as well as right and wrong actions. This research used a literature review methodology to examine the implementation of Islamic business principles in enhancing integrity and honesty. “The findings indicate that the implementation of Islamic business ethics principles, including justice, accountability, and honesty, fosters harmonious relationships among company participants and stakeholders. The case study of the Roti Gembul enterprise illustrates that the incorporation of Islamic principles in business practices emphasizes not only financial gains but also spiritual rewards and societal contributions. This result affirms that comprehending and applying Islamic business principles is crucial for Muslim entrepreneurs to attain enduring success and get blessings in the hereafter.